Responsibility to maintain parents in the light of Maqasid al-Shari'ah - Hj Ibrahim, Badruddin (Jabatan Kehakiman Syariah Malaysia & Ahmad Ibrahim Kulliyyah of Laws, 2021)
Parents are the origin (usul) of children. They are the foundation of a family institution that establishes a family as with their unification, a family institution begins. Children are the result of such legal unification and it develops the family into a bigger circle. Under Islamic law, parents are given a special place especially for love, obedience and respect. On the day a man and a woman unite as husband and wife, Islamic law has outlined their rights and responsibilities to be fulfilled and discharged by both. Such rights and duties are further defined when it comes to the relationship between parents and children. One of the rights of parents is to be maintained by children especially in their old age where at that time they are weak and unable to maintain themselves. This paper is to examine the responsibility to maintain parents in the light of maqasid al-Shari‘ah under Islamic law. The paper will further analyse what are the values that Islamic law wishes to protect when imposing the responsibility to maintain parents. The paper adopts a qualitative research methodology which is a library research based on the theory of Islamic jurisprudence. It is hoped that the findings of the research will provide a clear picture on the responsibility to maintain parents in the light of maqasid al-Shari‘ah and will benefit all readers and researchers.